Ujian Kesetiaan Persembahan Dimasa Pandemi Covid-19 Berdasarkan Maleakhi 3:10 - Saul Situmeang; Rolyana Ferinia; Stimson Hutagalung (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
The Covid-19 pandemic has disrupted the financial structure of church members. The dilemma when it comes to paying offerings and tithing or making a living. Based on this dilemma gap, the purpose of this study is to describe the offerings and tithes of the Natar district congregation and to analyze the faithfulness of church members in paying tithes and offerings. This research method was qualitative with a descriptive approach. The data collection technique used were financial data from the church treasurer about offerings and tithes giver. The first stage was to create a data graph to see the giving unit and the second stage was analyze the economic situation of the congregation and the level of faithfulness of the congregation. The results of the ongoing COVID-19 pandemic research increase the faith of church members through the provision of integrated offerings that increase during the pandemic and the giving of tithes given every month. Evidence of increased faith is that they are more enthusiastic and active in preaching the gospel.